Physiological significance of WDR45, a responsible gene for β-propeller protein associated neurodegeneration (BPAN), in brain development - Mariko Noda (Nature Portfolio, 2021)
Abstract WDR45 plays an essential role in the early stage of autophagy. De novo heterozygous mutations in WDR45 have been known to cause β-propeller protein-associated neurodegeneration (BPAN), a subtype of neurodegeneration with brain iron accumulation (NBIA). Although BPAN patients display global developmental delay with intellectual disability, the neurodevelopmental pathophysiology of BPAN remains largely unknown. In the present study, we analyzed the physiological role of Wdr45 and pathophysiological significance of the gene abnormality during mouse brain development. Morphological and biochemical analyses revealed that Wdr45 is expressed in a developmental stage-dependent manner in mouse brain. Wdr45 was also found to be located in excitatory synapses by biochemical fractionation. Since WDR45 mutations are thought to cause protein degradation, we conducted acute knockdown experiments by in utero electroporation in mice to recapitulate the pathophysiological conditions of BPAN. Knockdown of Wdr45 caused abnormal dendritic development and synaptogenesis during corticogenesis, both of which were significantly rescued by co-expression with RNAi-resistant version of Wdr45. In addition, terminal arbors of callosal axons were less developed in Wdr45-deficient cortical neurons of adult mouse when compared to control cells. These results strongly suggest a pathophysiological significance of WDR45 gene abnormalities in neurodevelopmental aspects of BPAN.